1969
DOI: 10.12669/pjms.301.4266
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotherapy with and without bone debridement in diabetic foot osteomyelitis: a retrospective cohort study

Abstract: Background and Objective: The treatment of diabetic foot osteomyelitis (DFO) is a controversial issue, with disagreement regarding whether the best treatment is surgical or conservative. The purpose of this study was to compare the outcome of patients with DFO who were treated with antibiotherapy alone and those who underwent concurrent minor amputation. Methods: Hospital records of patients who were diagnosed as having DFO within a 2-year study period were retrospectively reviewed. Patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 0 publications
1
30
1
3
Order By: Relevance
“…We identified 11 studies conducted in patients with diabetic foot osteomyelitis. One study included results on the value of bone biopsy, another was a substudy of patients with soft tissue infections., and another was an RCT of 6 versus 12 weeks of antibiotic therapy without surgery …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 11 studies conducted in patients with diabetic foot osteomyelitis. One study included results on the value of bone biopsy, another was a substudy of patients with soft tissue infections., and another was an RCT of 6 versus 12 weeks of antibiotic therapy without surgery …”
Section: Resultsmentioning
confidence: 99%
“…Saltoglu et al; Lipsky et al; Lauf et al; Grayson et al; Erstad et al; Lipsky et al; Lipsky et al; Lipsky et al; Lázaro‐Martínez et al; Ulcay et al; Tone et al, Li et al…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Surgical resection of infected bone has long been the standard treatment of osteomyelitis, but over the past two decades, evidence from several retrospective case series, one retrospective cohort study, and one prospective controlled study has demonstrated that in properly selected patients, antibiotic therapy alone is effective. While treatment of DFO with antibiotics without surgical resection of bone may be considered for any patient with DFO, based on published data, the strongest cases for considering nonsurgical treatment include patients with limited DFO of the forefoot, who are medically stable, for whom there is no other mechanical need for surgical treatment of the foot, and for whom there is an appropriate antibiotic regimen .…”
Section: Treatmentmentioning
confidence: 99%
“…Mean duration of antibiotic treatment was surprisingly short, ranging from 6 to 42 days . The investigators of the two studies of predominantly surgery versus antibiotic therapy prescribed antibiotics for up to 90 days in the antibiotics group and 10 days for the surgery group in the RCT and 45 days and 48 days in the cohort study , respectively. The quality of most, but not all (Table S1), of these studies was generally good, and each reported no significant difference in outcome between the treatment arms or between oral and parenteral route of administration.…”
Section: Resultsmentioning
confidence: 99%